Electronic Health Record Interoperability as Realized in the Turkish Health Information System - Dogac, A.; Yuksel, M.; Avcl, A.; Ceyhan, B.; Hülür, Ü.; Eryllmaz, Z.; Mollahaliloğlu, S.; Atbakan, E.; Akdağ, R. (Methods of Information in Medicine, 2011)
Objectives: The objective of this paper is to describe the techniques used in developing the National Health Information System of Turkey (NHIS-T), a nation-wide infrastructure for sharing electronic health records (EHRs).Methods: The UN/CEFACT Core Components Technical Specification (CCTS) methodology was applied to design the logical EHR structure and to increase the reuse of common information blocks in EHRs.Results: The NHIS-T became operational on January 15, 2009. By June 2010, 99% of the public hospitals and 71% of the private and university hospitals were connected to NHIS-T with daily feeds of their patients’ EHRs. Out of the 72 million citizens of Turkey, electronic healthcare records of 43 million citizens have already been created in NHIS-T. Currently, only the general practitioners can access the EHRs of their patients. In the second phase of the implementation and once the legal framework is completed, the proper patient consent mechanisms will be available through the personal health record system that is under development. At this time authorized health-care professionals in secondary and tertiary healthcare systems can access the patients’ EHRs.Conclusions: A number of factors affected the successful implementation of NHIS-T. First, all stakeholders have to adopt the specified standards. Second, the UN /CEFACT CCTS approach was applied which facilitated the development and understanding of rather complex EHR schemas. Finally, the comprehensive testing of vendor-based hospital information systems for their conformance to and interoperability with NHIS-T through an automated testing platform enhanced substantially the fast integration of vendor-based solutions with the NHIS-T.
Keywords: Electronic healthcare records; interoperability; health information exchange; standards; UN/ CEFACT CCTS; HL7 CDA; eHealth conformance and interoperability testing